Internet Addiction as Predictor in Marital Relationship among a Sample of Divorced Women - Harahsheh, Ahmad Hasan Muhareb (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2025)
This study investigates the predictive relationship between Internet addiction and marital incompatibility among a sample of divorced women. Given the rapid technological advancements and the pervasive influence of the Internet on marital compatibility, this research examines the extent to which Internet addiction serves as a predictor for marital enhancers and inhibitors of compatibility. Utilizing a sample of 123 divorced women, the study employs the Internet Addiction Scale (IAS) (Cronbach’s alpha= .86) and the Marital Compatibility Inhibitors and Enhancers Scale (MCIES) (Cronbach’s alpha= .76, .72, respectively). The findings reveal a high prevalence of Internet addiction (M=4.23, SD=.57), elevated levels of inhibitors (M=4.18, SD=.64) affecting marital adjustment, and a diminished presence of enhancers (M=1.75, SD=.60) promoting marital compatibility. Statistical analysis demonstrates significant and robust correlations between Internet addiction and both marital adjustment inhibitors (r = .789) and enhancers (r = -.991) among divorced women. Furthermore, Internet addiction accounts for 61.9% of the variance in inhibitors and negatively correlates with 98.2% of the variance in enhancers. The study concluded that the Internet addiction affects the marital relationship, and thus negatively affecting the cohesion of the family and society.